2023
DOI: 10.1111/1477-8947.12321
|View full text |Cite
|
Sign up to set email alerts
|

The valuation of ecosystems services in the Inner Mongolia Autonomous Region of China

Yu Fan,
Qiong Wu,
Changgeng Jia
et al.

Abstract: The valuation of ecosystem services is a powerful strategy on measuring the relations between natural resources and human capitals, to achieve the goal of protecting and promoting the positive contribution of nature. Gross Ecosystem Product (GEP) is a series of statistics that incorporates the monetary value of ecosystem services, which turns the ecological data comparable to GDP. As a case study of the relationship between ecosystem services and economic development, this work focused on the Inner Mongolia Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…At present, the relevant research on GEP accounting is only at the evaluation level, failing to clarify the internal driving factors of GEP changes, which is not conducive to the application of GEP in the management decision-making process 25 28 . Previous researchers had shown that urbanization is an important factor affecting ecological quality 20 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, the relevant research on GEP accounting is only at the evaluation level, failing to clarify the internal driving factors of GEP changes, which is not conducive to the application of GEP in the management decision-making process 25 28 . Previous researchers had shown that urbanization is an important factor affecting ecological quality 20 .…”
Section: Introductionmentioning
confidence: 99%